The Role of Research Work in the Training of Master Students Studying at Technical University; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Ruchina A. V. Aleksandra Viktorovna; Kuimova M. V. Marina Valerievna; Polyushko D. A. Denis; Sentsov A. E. Arkadii; Zhang Xue Jin (2015, 2015)
Title screen